2017
DOI: 10.18869/nrip.irj.15.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between a Genetic Polymorphism in ACTN3 and Elite Sport Performance Among Iranian Soccer Players

Abstract: Objectives: Polymorphisms in α-actinin-3 (ACTN3) gene are considered to be important in the genetic predisposition to human athletic performance. Most of the activities in soccer such as jumping, striking the ball, and running are considered plyometric and explosive. Performance power during such activities depends on the strength of the muscles involved. Therefore, high muscle strength is considered crucial for soccer players. The primary objective of this study was to ascertain the association between ACTN3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The relationship between ACTN3 and ACE polymorphisms and athletic performance is currently equivocal. Honarpour et al [15] found that football players had higher frequencies of ACTN3 577RR and 577RX genotypes than that of the general population. Furthermore, it has been observed that athletes with the ID/II genotype perform better on endurance tests [20].…”
Section: Endurancementioning
confidence: 99%
See 4 more Smart Citations
“…The relationship between ACTN3 and ACE polymorphisms and athletic performance is currently equivocal. Honarpour et al [15] found that football players had higher frequencies of ACTN3 577RR and 577RX genotypes than that of the general population. Furthermore, it has been observed that athletes with the ID/II genotype perform better on endurance tests [20].…”
Section: Endurancementioning
confidence: 99%
“…Endurance. The most studied polymorphisms were ACTN3 [1,15,20], ACE [20,21], AGT and AMPD [20], MTHFR [22], and GST [21]. Overall, 4 studies included young male football players and 1 involved youth female football players [1].…”
Section: Performancementioning
confidence: 99%
See 3 more Smart Citations